Proximal and distal gastro‐oesophageal reflux in chronic obstructive pulmonary disease and bronchiectasis. (25th December 2013) - Lee, Annemarie L.; Button, Brenda M.; Denehy, Linda; Roberts, Stuart J.; Bamford, Tiffany L.; Ellis, Samantha J.; Mu, Fi‐Tjen; Heine, Ralf G.; Stirling, Robert G.; Wilson, John W.
Abstract: Background and objective: The aims of this observational study were (i) to examine the prevalence of symptomatic and clinically silent proximal and distal gastro‐oesophageal reflux (GOR) in adults with chronic obstructive pulmonary disease (COPD) or bronchiectasis, (ii) the presence of gastric aspiration, and (iii) to explore the possible clinical significance of this comorbidity in these conditions. Methods: Twenty‐seven participants with COPD, 27 with bronchiectasis and 17 control subjects completed reflux symptom evaluation and dual‐channel 24 h oesophageal pH monitoring. In those with lung disease, pepsin levels in sputum samples were measured using enzyme‐linked immunosorbent assay, with disease severity (lung function and high‐resolution computed tomography) also measured. Results: The prevalence of GOR in COPD was 37%, in bronchiectasis was 40% and in control subjects was 18% ( P = 0.005). Of those diagnosed with GOR, clinically silent reflux was detected in 20% of participants with COPD and 42% with bronchiectasis. While pepsin was found in 33% of COPD and 26% of bronchiectasis participants, the presence of pepsin in sputum was not related to a diagnosis of GOR based on oesophageal pH monitoring in either condition. Neither a diagnosis of GOR nor the presence of pepsin was associated with increased severity of lung disease in COPD or bronchiectasis. Conclusions: The prevalence of GOR in COPD or bronchiectasis is twice that of the control population, and the diagnosis could not be based on symptoms alone. Pepsin was detected in sputum in COPD and bronchiectasis, suggesting a possible role of pulmonary aspiration, which requires further exploration. Abstract : The prevalence of gastro‐oesophageal reflux in adults with chronic obstructive pulmonary disease or bronchiectasis is twice as high compared with individuals without lung disease. The findings of this observational study suggest that gastro‐oesophageal reflux is a common comorbidity across the disease spectrum in adults with these lung conditions.